Theoretical and Empirical Analyses of an Improved Harmony Search Algorithm Based on Differential Mutation Operator - Longquan Yong; Sanyang Liu; Jianke Zhang; Quanxi Feng (Journal of Applied Mathematics)
Harmony search (HS) method is an emerging metaheuristic optimization algorithm. In this paper, an improved harmony search method based on differential mutation operator (IHSDE) is proposed to deal with the optimization problems. Since the population diversity plays an important role in the behavior of evolution algorithm, the aim of this paper is to calculate the expected population mean and variance of IHSDE from theoretical viewpoint. Numerical results, compared with the HSDE, NGHS, show that the IHSDE method has good convergence property over a test-suite of well-known benchmark functions.